Time trends of vitamin D concentrations in northern Sweden between 1986 and 2014: a population-based cross-sectional study - Summerhays, Eva (Eur J Nutr, 2019)
PURPOSE: Vitamin D, produced through cutaneous photosynthesis or ingested via foods or supplements, has generated considerable research interest due to its potential health effects. However, epidemiological data on the time trends of vitamin D status are sparse, especially from northern Europe. We examined the time trend of vitamin D concentrations in northern Sweden between 1986 and 2014. METHODS: We used data on 11,129 men and women (aged 25–74 years) from seven population-based surveys (the Northern Sweden MONICA study), recruited between 1986 and 2014. Serum vitamin D (25-hydroxyvitamin D) status was measured using a one-step immunoassay (Abbott Architect). Multivariable linear regression models, adjusted for age, sex, and a number of other variables, were used to estimate the time trend of vitamin D concentrations. RESULTS: The mean value of vitamin D in the entire study population was 19.9 ng/mL [standard deviation (SD) 7.9], with lower values in men (19.4 ng/mL; SD 7.5) than in women (20.5 ng/mL; SD 8.2). Using the survey in 1986 as reference category, the multivariable-adjusted mean difference [95% confidence interval (CI)] in ng/mL was 2.7 (2.2, 3.3) in 1990, 3.2 (2.7, 3.7) in 1994, 1.6 (1.0, 2.1) in 1999, − 2.0 (− 2.5, − 1.4) in 2004, 1.0 (0.4, 1.5) in 2009, and 3.1 (2.5, 3.6) in 2014. CONCLUSION: In this large cross-sectional study, we observed no clear upward or downward trend of vitamin D concentrations in northern Sweden between 1986 and 2014. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00394-019-02142-x) contains supplementary material, which is available to authorized users.